2022
DOI: 10.1016/j.esxm.2022.100517
|View full text |Cite|
|
Sign up to set email alerts
|

Cost of Intralesional Collagenase Clostridium Histiolyticum Therapy Versus Surgery for the Management of Peyronie's Disease: A Claims-Based Analysis (2009–2019)

Abstract: Background Collagenase Clostridium histolyticum (CCH), which was approved by the FDA for the treatment of Peyronie's disease (PD) in 2013, may obviate the need for surgery but its historically high cost must be considered when offering CCH vs surgical intervention to affected patients. Aim To compare trends of intralesional injections vs surgical treatment for PD and assess the contemporary cost of treatment with CCH vs surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…(4) Es esencial mencionar que lamentablemente la viabilidad económica e implementación de la CCH es inversamente proporcional a sus beneficios, lo que ha resultado en tasas bajas de finalización del tratamiento y lo que dificulta su implementación en países cuyo sistema de salud no oferta esta opción terapéutica. (29) Ahora bien, aunque esto corresponde a una limitación, el uso intralesional de otros agentes menos efectivos como verapamilo o interferón A2b se pueden agregar a un protocolo que implemente simultáneamente la terapia mecánica e IPDE-5, convirtiéndose en una opción rentable, segura y efectiva a los pacientes que se rehúsan a la intervención quirúrgica y residen en países en vías de desarrollo.…”
Section: Discussionunclassified
“…(4) Es esencial mencionar que lamentablemente la viabilidad económica e implementación de la CCH es inversamente proporcional a sus beneficios, lo que ha resultado en tasas bajas de finalización del tratamiento y lo que dificulta su implementación en países cuyo sistema de salud no oferta esta opción terapéutica. (29) Ahora bien, aunque esto corresponde a una limitación, el uso intralesional de otros agentes menos efectivos como verapamilo o interferón A2b se pueden agregar a un protocolo que implemente simultáneamente la terapia mecánica e IPDE-5, convirtiéndose en una opción rentable, segura y efectiva a los pacientes que se rehúsan a la intervención quirúrgica y residen en países en vías de desarrollo.…”
Section: Discussionunclassified
“…Only two of the studies showed no change after subsequent therapy [39,44]. The average annual cost of verapamil is about US$60 according to 2019 US data [45].…”
Section: Therapeutical Ultrasoundmentioning
confidence: 99%
“…There is also a significant price difference between the US and Europe. For example, an intralesional application in a US article is listed as US$300 [45]. Although intralesionally administered drugs are theoretically expected to be more effective than oral drugs due to the targeted direct effect in the penile plaque, published clinical studies show mixed results and this reflects the heterogeneous nature of PD with different manifestations.…”
Section: Botulinum Toxin (Botox)mentioning
confidence: 99%